The digitalization of classic sports toward Esports: managerial underpinnings, potential benefits, obstacles and the effects of Covid-19 - Möhring, M. (2020)
This thesis provides a consistent presentation of how the phenomenon of Esport has evolved through times and generations, from the first amateur competitions gathering a handful of friends playing on arcades machines to massive international events gathering hundreds of thousands of fans in gigantic stadiums. More than the observable evolution, this paper also addresses the potential future evolution of the sector. Naturally, along with this development and expected evolution come business opportunities. After snapshotting the market of Esports, the most popular business and marketing strategies are presented. As a last part for this paper, the emphasis is put on the case of the digitalization of classic sports toward Esports and the impact of the covid-19 pandemic on it. The goal of this practical section is to conduct in-depth interviews with top-managers from the sport and Esport industries in order to analyze their opinion on this association between the classic sport world and the new one of Esports. The most relevant trends and points of view emerging from these discussion are then discussed, depicting a clearer picture of how the world of professional gaming is perceived by professionals. This paper concludes that, in the future, Esports is likely to profoundly change its relation to classic sport and to become a very different industry than what it is today. The change of generation, the rise of new technologies like virtual reality and the new customer expectations will lead to a deep change in the industry`s organization, making Esport a major actor of the entertainment in our society.